The Influence of Using Audio Visual Media-Based Language on AUD Linguistic Intelligence at RA Al-Ishlah, Perkebunan Bekiun Village, Kuala District, Langkat Regency - Fadillah, Adel; Ningsih, Arie Dwi (Lembaga Riset Mutiara Akbar, 2025)
The purpose of this study is to determine the impact of the use of audiovisual media-based language on the linguistic intelligence of children in RA Al-Ishlah, Bekiun Plantation Village. The research method applied in this study is quantitative research with a pre-experimental approach. This research was carried out in the odd semester of the 2025/2026 school year at RA Al-Ishlah, which is located in Bekiun Plantation Village, Bekiun Plantation District. Kuala, Langkat Regency, North Sumatra 20762. The population in this study is 45 students of group B RA Al-Ishlah located in Bekiun Plantation Village, which is 15 children. The sampling method used in this study is a purpossive sampling technique. The methods for data collection applied include observation and documentation. The data analysis technique in this study uses simple regression analysis using SPSS 23. The results showed that Early Childhood linguistic intelligence (AUD) increased after using audio-visual media in learning activities. This shows that the use of audio-visual media-based language affects children's linguistic intelligence so that children can ask questions, answer questions, tell stories, and provide ideas/ideas in learning. Based on this supported by hypothesis testing, it can be concluded that there is an influence of the use of audio-visual media on early childhood linguistic intelligence in RA Al-Ishlah, Bekiun Plantation Village, Kuala District, Langkat has a significant effect.